NUMERICAL INVESTIGATION OF NATURAL CONVECTION AROUND A CIRCULAR CYLINDER PLACED IN A CAVITY FILLED WITH NANOFLUID BY CHANGING THE LOCATION AND RADIUS - A. Fereidun; A.A. Abbasian Arani; A.A. Abbasian Arani; M. Hemmat Esfe; A. Zare Ghadi (مجله مدل سازی در مهندسی, 2013)
In this article, a numerical study was conducted to examine the effect of location and diameter of the inner cylinder on laminar natural convection flow fields and temperature distribution around a circular body inserted square cavity. In order to study different situations, the radius of obstacle varied from 0.2 to 0.3 length of square, the Rayleigh number between 103 to 107 and solid contraction of nanofluid with diameter of 40 nanometers changed from 0 to 8%. The above parameters can be used as a control parameter for heat transfer, fluid flow and temperature distributions. The results show that in situations where the heated circular body is close to the lower wall of the cavity, the change of temperature field and streamlines is more noticeable than any other position. On the other hand, Nusselt number and consequently heat transfer increases with increasing of solid volume fraction of nanoparticles. Also when the radius of the body decrease from 0.3L to 0.15L, the Nusselt number increase by 79.15 percent.